Political Economy and the Canadian Working Class: Marxism or Nationalist Reformism? - Smith, Murray (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2000)
Abstract The dominant, nationalist tradition of left-wing political economy in Canada has always stood as an obstacle to the articulation of a Marxist political economy of Canada capable of contributing to the development of a class struggle, socialist politics. The evolution of the "New Canadian Political Economy" that emerged in the 1960s is traced and its main schools of thought are delineated. Against the nationalist preoccupations of the NCPE, the argument is made that the economic troubles of Canada in the past quarter century are attributable to the "normal" crisis tendencies of an advanced capitalist economy (as analyzed by Marx) and should not be seen as the product of "foreign domination" of the Canadian economy.